PRARANCANGAN PABRIK MONOETHYLAMIN DARI ETHANOL DAN AMONIAK KAPASITAS 25.000 TON / TAHUN - , FERDIANSYAH ARYANTO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Monoethylamine is made by reacting ethanol and ammonia in a fixed bed multitube reactor on continuous condition with the Co 34% catalyst in alumina. Reaction is being occured in the gases phase at temperature from 463,05 to 515,26 K and pressure of 18 atm. Heat arising during the reaction taken by the cooling water flowing in the shell. The monoethylamine plant from ethanol and ammonia is designed with the capacity of 25.000 tons/year and operated continuously for 330 days/year and 24 hours / day. The product obtained are monoethylamine with 99,66% purity, diethylamine with 99,62% purity, and triethylamine with 89,63% purity. The raw materials used are 29594,71 ton/year of ethanol 95%, 14887,76 ton/year of ammonia 99,5%, and 33,20 ton/year of hydrogen. The plant will be located in Gresik, East Java, on a land area of 15.000 m2 with 168 employees. The requirement amount of steam is 5782,56 kg/jam, water is 849,86 m3/jam, fuel is 604,83 kg/jam,instrument air is 111,53 m3/jam, and 1549,52 kWatt of electricity. Fixed Capital Investment (FCI) needed is US$10.758.947,31 and Rp54.742.406.925,33, working capital is US$2.513.363,91 and Rp 159.503.844.960,73, manufactured cost is US$ 14.177.950,24 and Rp445.051.677.246,07, general expense is US$7.728.758,16 and Rp1.840.341.752,14, profit before tax is Rp78.144.682.558,96 and profit after tax is Rp39.072.341.279,48. From the calculation obtained, Return on Investment (ROI) before taxes is 48,14% and after task is 24,07%. Pay Out Time (POT) before taxes is 1,72 years and after task is 2,94 years, Break Even Point (BEP) is 42,70%, Shut Down Point (SDP) is 25,70%, and Discounted Cash Flow Rate Of Return (DCFRR) is 18,19%. Based on the data above, The Monoethylamine Plant from Ethanol and Ammonia with capacity 25.000 tons/year is interesting and feasible for further study.